Mass Propagation System of Strawberry (Fragaria _ ananassa) Microshoots by Liquid Shake Culture - Pana Lohasupthawee; Prakarn Chomboon (My University, 2021)
The future of strawberry propagation and sales is very positive, so an efficient mass propagation system for strawberry (Fragaria × ananassa) was developed in this study. Strawberry leaf explants successfully induced green compact calli in semi-solid MS medium supplemented with 1 mg/l 2,4-D and 0.5 mg/l BA within 2 weeks. Subculture the calli in semi-solid MS medium supplemented with 1 mg/l TDZ and 0.2 mg/l 2,4-D produced 3.8 microshoots per callus within 49-56 days. These leaf-derived calli with adventitious shoots were cultured with 0.1 mg/l GA_3 and shaken at 120 rpm. The number of shoots increased from 15.3 shoots to 43.6 shoots per culture (100 ml) within 2 weeks, but all were hyperhydric shoots. Hyperhydric shoots recovered to normal shoots within 1 month when cultured on semi-solid MS medium with 8 g/l agar. Shoots formed roots on semi-solid MS medium supplemented with 0.5 mg/l IBA within 2 weeks. Rooted plantlets were acclimatized for 1 week before being transferred to the field at Bendito farm, where the strawberry plants were grown until maturity.
Keywords: Subculture (biology); Fragaria; Callus; Plant tissue culture and regeneration